The Role of Improved O&OD Methodology in Promoting Social Economy in Tanzania: A Solution to Sustainable Community Social Development Projects? - Rugeiyamu, Rogers (Local Administration Journal, 2021)
This study uses Participatory Local Social Development (PLSD) to assess whether Improved Opportunities & Obstacles to Development (O&OD) is an effective methodology for promoting sustainable social economy in Tanzania. The study was conducted at Maseyu village in the Morogoro region of Tanzania. A case study design was applied whereby data were collected through observation and interviews and analyzed using content analysis approach. The results revealed that improved O&OD can be an answer to community social development projects sustainability in Tanzania. This is a prerequisite of anticipated social economy if communities change their current mindset of “waiting for the government/development partners to do for them” to “start doing by themselves”. The study recommends communities use the Ward Facilitators (WFs) and Community Facilitators (CFs) proposed by the Improved O&OD Guidelines as a tool to change people’s mindsets to ensure that they plan, implement, and sustain self-initiated projects.